1982
DOI: 10.1128/jcm.16.1.86-91.1982
|View full text |Cite
|
Sign up to set email alerts
|

Direct Testing of Blood Cultures for Detection of Streptococcal Antigens

Abstract: A direct, rapid, and simple method for the detection of streptococcal antigens of Lancefield groups A, B, C, D, and G from blood cultures was developed by using a coagglutination test. Fifty-five clinical specimens and 117 simulated blood cultures containing gram-positive cocci were tested. Out of 6,261 clinical blood cultures screened, 55 cultures from 53 patients were positive, with organisms resembling streptococci, by Gram stain. Of these cultures, 78% (43 of 55) were pure cultures of streptococci, and 22%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…In our routine diagnostic laboratory, pneumococci have regularly been observed to react with a co-A reagent prepared with antistreptococcal group C antiserum, and this cross-reaction has also been reported by others (5,20,30). Since both streptococcal group C polysaccharide and pneumococcal F antigen are Forssman antigens (6, 7), we investigated whether this common feature could explain these cross-reactions.…”
Section: Discussionmentioning
confidence: 55%
“…In our routine diagnostic laboratory, pneumococci have regularly been observed to react with a co-A reagent prepared with antistreptococcal group C antiserum, and this cross-reaction has also been reported by others (5,20,30). Since both streptococcal group C polysaccharide and pneumococcal F antigen are Forssman antigens (6, 7), we investigated whether this common feature could explain these cross-reactions.…”
Section: Discussionmentioning
confidence: 55%
“…Some of the culture-positive, COA-negative results may have been due to the numbers of organisms present or the antigen concentration in the clinical specimens, which may have been below the detection limit for COA. Olcen (8) found that he could not detect concentrations below 105 CFU/ml, whereas Wetkowski et al (13) found that 107 to 108 CFU/ml were necessary for detection of streptococci in positive blood cultures. Colony counts were known for two of the N. meningitidis specimens; one specimen did not grow on solid media and the organism was recovered only in broth, the other produced 120 colonies or ca.…”
Section: Discussionmentioning
confidence: 98%
“…These procedures confirmed the false cross-reactions and were in complete agreement with the LA results obtained on the same cultures. Although all strains studied by Wellstood were tested by the Lancefield precipitin method (15), the reference procedure used is not clearly stated in the study by Wetkowski et al (16). b All false-positive reactions for S. pneumoniae were with the group C reagent.…”
Section: Methodsmentioning
confidence: 99%
“…The serological grouping of streptococci has become technically simple with the development of immunofluorescent (IF), coagglutination, and latex agglutination (LA) techniques (1, 3,5,6,13,15,16). Furthermore, rapid identification of bacteria from a variety of sources, especially blood and body fluids, has become a subject of intensive investigation in recent years (9, 9a, 14-16).…”
mentioning
confidence: 99%
See 1 more Smart Citation